2014
DOI: 10.1111/febs.12839
|View full text |Cite
|
Sign up to set email alerts
|

NMR observation of HIV‐1 gp120 conformational flexibility resulting from V3 truncation

Abstract: The envelope spike of HIV-1, which consists of three external gp120 and three transmembrane gp41 glycoproteins, recognizes its target cells by successively binding to its primary CD4 receptor and a coreceptor molecule. Until recently, atomic-resolution structures were available primarily for monomeric HIV-1 gp120, in which the V1, V2 and V3 variable loops were omitted (gp120 core ), in complex with soluble CD4 (sCD4). Differences between the structure of HIV gp120 core in complex with sCD4 and the structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Binding of ECL2S to mut gp120 core (gp120 core molecule lacking V1, V2 and V3 containing four mutations that alleviated the aggregation problem) and to mut gp120 core (+V3) ( mut gp120 core lacking only V1 and V2) in the presence or absence of a 27‐residue CD4 peptide mimic, CD4M33 , was measured using surface plasmon resonance (SPR) at 25 °C. Biotin was added to the peptide's N‐terminus to enable immobilization of the peptide on a streptavidin‐coated SPR chip.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Binding of ECL2S to mut gp120 core (gp120 core molecule lacking V1, V2 and V3 containing four mutations that alleviated the aggregation problem) and to mut gp120 core (+V3) ( mut gp120 core lacking only V1 and V2) in the presence or absence of a 27‐residue CD4 peptide mimic, CD4M33 , was measured using surface plasmon resonance (SPR) at 25 °C. Biotin was added to the peptide's N‐terminus to enable immobilization of the peptide on a streptavidin‐coated SPR chip.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of CD4M33, a K D of 6 AE 4 9 10 À6 M was determined, offering only a rough estimate of the K D . A reliable K D for mut gp120 core (+V3) was not determined due to partial dimerization of the mut gp120 core (+V3)/CD4M33 complex [26]. Similar K D values for ECL2S binding to the mut gp120 core / CD4M33 were measured at pH 6 and pH 6.5 (K D values of 7 AE 3 and 7.5 AE 3 9 10 À6 M, respectively), suggesting that binding of ECL2S to mut gp120 core / CD4M33 is not influenced by pH between 6 and 7.…”
Section: The Ecl2s Peptide Is Helicalmentioning
confidence: 99%
See 1 more Smart Citation
“…When NN‐T20‐NITN binding to mut gp120 core (+V3) and mut gp120 core in complex with CD4M33 was compared, we found that V3 improved NN‐T20‐NITN binding by five‐fold. However, it is possible that the stronger mut gp120 core (+V3)/CD4M33 binding to NN‐T20‐NITN is in part the result of the previously observed aggregation of mut gp120 core (+V3)/CD4M33 . Therefore, this contribution of V3 to gp120 binding to NN‐T20‐NITN, in the presence of CD4M33, may or may not be significant.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, the NN-T20-NITN portion of the modified T20 peptide corresponds to residues 638-673 of gp41 of HIV-1. To map the segment within the NN-T20-NITN peptide that interacts with gp120, we used 1 H-15 N-heteronuclear single quantum coherence (HSQC) measurements of uniformly 15 N labeled (U-15 N) NN-T20-NITN in the presence and absence of gp120. In general, the 1 H-15 N-HSQC spectrum of a 15 N labeled peptide in complex with a much larger protein discriminates residues within the segment that interact with the protein from those peptide residues outside this region.…”
Section: Nn-t20-nitn Binding To R5 Gp120mentioning
confidence: 99%